2017
DOI: 10.2337/db17-0249
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Corneal Sensitivity and Increase in Nerve Density and Wound Healing in Diabetic Mice After PEDF Plus DHA Treatment

Abstract: Diabetic keratopathy decreases corneal sensation and tear secretion and delays wound healing after injury. In the current study, we tested the effect of treatment with pigment epithelium-derived factor (PEDF) in combination with docosahexaenoic acid (DHA) on corneal nerve regeneration in a mouse model of diabetes with or without corneal injury. The study was performed in streptozotocin-induced diabetic mice (C57BL/6). Ten weeks after streptozotocin injection, diabetic mice showed significant decreases of corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 53 publications
2
72
2
Order By: Relevance
“…Identification of novel RvD6si in mouse tears. The biological activities of PEDF + DHA have been revealed previously by our laboratory [20][21][22][23][24] . A mechanistic link of PEDF + DHA action on corneal nerve regeneration has been uncovered with the activation of the iPLA2ζ and the increased expression of the neurotrophic factors, brain-derived growth factor (BDNF) and nerve growth factor (NGF), and the axon growth guidance semaphorin 7a (Sema7A) released in tears 25 .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Identification of novel RvD6si in mouse tears. The biological activities of PEDF + DHA have been revealed previously by our laboratory [20][21][22][23][24] . A mechanistic link of PEDF + DHA action on corneal nerve regeneration has been uncovered with the activation of the iPLA2ζ and the increased expression of the neurotrophic factors, brain-derived growth factor (BDNF) and nerve growth factor (NGF), and the axon growth guidance semaphorin 7a (Sema7A) released in tears 25 .…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have shown that PEDF + DHA promotes corneal wound healing in rabbit 20,21 , and in normal and diabetic mice 24,25 after experimental surgery. We tested the ability of RvD6s (either RvD6 or RvD6si) in stimulating corneal wound healing.…”
Section: Rvd6si Enhances Corneal Wound Healing and Recovery Of Corneamentioning
confidence: 94%
See 1 more Smart Citation
“…Cats often suffer from herpetic keratitis, an ocular surface disease known to damage corneal nerves . Our previous studies have shown in rabbits and mice that topical treatment with a combination of the neurotrophic factor pigment epithelium‐derived factor (PEDF) and the omega‐3 fatty acid docosahexaenoic acid (DHA) stimulates the nerve regeneration after refractive surgery, diabetes, and herpesvirus‐1 infection . Recent studies to uncover the mechanism show an activation of the PEDF receptor that enhances the synthesis of docosanoids and neurotrophins .…”
Section: Discussionmentioning
confidence: 99%
“…19,33,34 Our previous studies have shown in rabbits and mice that topical treatment with a combination of the neurotrophic factor pigment epithelium-derived factor (PEDF) and the omega-3 fatty acid docosahexaenoic acid (DHA) stimulates the nerve regeneration after refractive surgery, diabetes, and herpesvirus-1 infection. [35][36][37] Recent studies to uncover the mechanism show an activation of the PEDF receptor that enhances the synthesis of docosanoids and neurotrophins. 38 While there are no studies on cat herpetic keratitis, this could represent an important future treatment to improve regeneration of nerves damaged by this disease.…”
Section: Discussionmentioning
confidence: 99%